(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Electronic sensing also called e-sensing refers to reproducing human senses using sensor arrays, emerged as a technical tool in quality control in food sector as well as important from commercial point of view. The International Union of Pure and Applied Chemistry (IUPAC) characterize synthetic sensors as “gadgets that transform chemical data into the form which can be further analysed. Variety of sensors are available for the analysis of food as they have their own advantages and disadvantages because of change in structural configuration in terms of input variable, working temperature and lifetime. Statistical programme are used to classify the samples into the groups for further analysis. Sensor innovation has grown quickly over the previous decade, and this has brought about a scope of various sensor groups and the advancement of complex microarray sensor gadgets. The most usually utilized sensors incorporate metal oxide semiconductor (MOS) sensors, conducting polymer (CP) sensors, optical sensors and piezoelectric sensors. The electronic nose, tongue, and eye are futuristic technologies that have been usedfor many years; they have been gaining market in different types of industries and can increasingly befound in the food area; their function is to determine sensory characteristics (smell, aroma, and flavour)and objective visuals, without the subjectivity that can be represented by sensory analysis by people (thestudy that can complement the analysis of machines, without being exclusive).The feeling of smell and taste coming from specific and non-specific atomic structures can be utilized to analyse the natureof food, drinks, and mixture of food items. Biological nose works actively to detect the quality of foods. We, as humanbeing can use our nose to judge the quality of food by the odor coming out of food whether it is healthy or unhealthy. Butstill there is probability of making a mistake to judge the quality and to categorize the food. So the researchers feel a needto design an electronic system which can judge quality of food accurately and precisely. Electronic noses are making outof strong sensors arrays to sense the smell of food products.